1973
DOI: 10.1021/ja00801a076
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an oxetene intermediate in the photoreaction of benzaldehyde with 2-butyne

Abstract: Detection of an Oxetene Intermediate in the Photoreaction of Benzaldehyde with 2-Butyne Sir:Numerous papers dating back to 1956 have been published that describe the photoproduction of enones on irradiation of carbonyl compounds in the presence of acetylenes.1 In all of these reports, an oxetene intermediate was assumed to have formed which was unstable and fragmented to the enone product. In none of these studies, however, was an oxetene isolated or detected.2 4602 (1971).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…The photoinduced [2+2] cycloaddition of an olefin to a carbonyl center has become a convenient methodology for oxetane preparation with high regio- and stereoselectivities. , As a result, the various synthetic and mechanistic aspects of this transformation, also known as the Paterno−Büchi reaction, have been the subject of numerous reviews. 1,2,4-6 Most importantly, the scope has been extended over the years to include enones , and quinones , as the carbonyl component and alkenes, dienes, and acetylenes as the olefinic counterpart. ,, As an example of the latter, the photocoupling of diphenylacetylene with p -benzoquinone 9 leads to the corresponding quinone methide in excellent yield via the labile oxetene formed by [2+2] cycloaddition: , Since such quinone methides are bright yellow, the more recent applications of this transformation have been directed to the preparation of highly colored extended conjugated systems for industrial applications …”
Section: Introductionmentioning
confidence: 99%
“…The photoinduced [2+2] cycloaddition of an olefin to a carbonyl center has become a convenient methodology for oxetane preparation with high regio- and stereoselectivities. , As a result, the various synthetic and mechanistic aspects of this transformation, also known as the Paterno−Büchi reaction, have been the subject of numerous reviews. 1,2,4-6 Most importantly, the scope has been extended over the years to include enones , and quinones , as the carbonyl component and alkenes, dienes, and acetylenes as the olefinic counterpart. ,, As an example of the latter, the photocoupling of diphenylacetylene with p -benzoquinone 9 leads to the corresponding quinone methide in excellent yield via the labile oxetene formed by [2+2] cycloaddition: , Since such quinone methides are bright yellow, the more recent applications of this transformation have been directed to the preparation of highly colored extended conjugated systems for industrial applications …”
Section: Introductionmentioning
confidence: 99%
“…Although the intramolecular alkyne carbonyl metathesis strategy has been applied largely in organic synthesis in last few years, the formation of an oxetene ring by intermolecular alkyne carbonyl metathesis was not extensively studied until now. In some examples photo irradiation was required for this purpose, whereas in others complex reaction conditions were entertained. One such example was found in which indium salt was taken as the catalyst for the alkyne‐aldehyde metathesis and 1‐butanol was required for the transformation as an additive .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, ion c ( m/z 315) was produced through a ring contraction and this ring contraction can be rationalized as a C(2)‐C(5) connection through an isocyanate molecule elimination as described above. The use of the ion c as a precursor ion yielded five main fragment ions d – h at m/z 297, 237, 207, 179 and 105, respectively, which indicated that the ion c is likely to exist in a dynamic equilibrium of the ring form and the open‐chain form, and the equilibrium should predominately shift to the open‐chain form because of the higher internal energy of the ring form 28. Thus, the loss of water, benzene and p ‐MeO‐Ph‐CHCHPh can be explained by the presence of c 2 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%